2017
DOI: 10.1111/1468-5973.12163
|View full text |Cite
|
Sign up to set email alerts
|

Crisis response strategies in Finland and Spain

Abstract: Crises are common in today's unpredictable environment rising the importance of crisis response strategies. Two societies in Europe are chosen: Finland, where trust in society is generalized to institutions, and Spain, where trust in society remains on the level of individuals. Using the results of the European Communication Monitor 2013 survey on crisis communication, we explored three hypotheses: “certain types of crises are often met with certain types of strategies,” “cultural context makes some crises mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
1
11
0
2
Order By: Relevance
“…Building on previous studies, like European Social surveys, democracy studies and societal comparisons, Finns would be more inclined to lean on structure and process, whereas the Spanish would be more likely to lean on individual legitimacy (Luoma-aho, Moreno & Verhoeven, 2017).…”
Section: Concluding Remarks and Outlookmentioning
confidence: 98%
“…Building on previous studies, like European Social surveys, democracy studies and societal comparisons, Finns would be more inclined to lean on structure and process, whereas the Spanish would be more likely to lean on individual legitimacy (Luoma-aho, Moreno & Verhoeven, 2017).…”
Section: Concluding Remarks and Outlookmentioning
confidence: 98%
“…Future research could empirically test the offered propositions using action research or other methodologies. Other potential research veins include examining if certain sense-giving message elements are more sensitive to variations in organizational cultures, parallel to the external work comparing external crisis messaging in Finland and Spain (Luoma-aho et al , 2017). Another avenue would be to examine the model across different industries to understand how similar cultures formed in different sectors might require messaging adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…The paper then offers an action research example of model application before presenting practitioner and researcher implications. Crisis management communication to external stakeholders is addressed by other authors (cf., Luoma-aho et al , 2017; Xu, 2018; Coombs, 2014) and is not this paper's focus.…”
mentioning
confidence: 99%
“…Some research has focused on the diversity within Western cultures in order to assess similarities and differences among Western countries. To be clear, such research has demonstrated the challenges of cultural differences within Western countries by examining their relative influence on public perceptions of a crisis (Taylor, 2000), the choice of crisis response strategies (Luoma-aho et al, 2017), and the views of crisis managers towards crises (Verhoeven et al, 2014).…”
Section: The Impact Of Societal Contexts On Crisis Communicationmentioning
confidence: 99%